Analisis Perilaku Tenaga Kerja Dalam Menjalankan Budaya K3 pada Proyek Konstruksi - Anggreyani, Ninis; Imron, Imron; Pramono, Heri (Journal of Accounting Law Communication and Technology, 2025)
This study aims to analyze the influence of occupational safety and health (OHS) culture on the implementation of construction projects, especially on the Khalifa IMS Tegal Elementary School construction project and to compare it with the classroom construction project at SMP Negeri 1 Kramat. OHS culture is one of the important factors in supporting worker safety and smooth project implementation. The research method used is a qualitative approach with data collection techniques through direct observation in the field and in-depth interviews. The results of the study indicate that the understanding and application of OHS culture are still not optimal in both projects, but the Khalifa IMS Tegal Elementary School project has begun to show initiative in implementing safety procedures even though they are not yet fully structured. Factors such as management commitment, OHS training, use of personal protective equipment (PPE), and routine supervision greatly influence the effectiveness of OHS culture in the field. It was also found that the lack of socialization and education of K3 caused the workforce to not have full awareness of the importance of occupational safety.